Pediatric burn contractures in low- and lower middle-income countries: A systematic review of causes and factors affecting outcome. Issue 5 (August 2020) - Meng, Fanyi; Zuo, Kevin J.; Amar-Zifkin, Alexandre; Baird, Robert; Cugno, Sabrina; Poenaru, Dan
Highlights: In developing countries, children with burns often fail to receive acute burn care. Inadequate acute burn care leads to debilitating joint and soft tissue contractures. Contractures are associated with poor SES, infrastructure, and maternal education. Abstract: In low- and lower middle-income countries (LMICs), timely access to primary care following thermal injury is challenging. Children with deep burns often fail to receive specialized burn care until months or years post-injury, thus suffering impairments from hypertrophic scarring or joint and soft tissue contractures. We aimed to examine the correlation between limited access to care following burn injury and long-term disability in children in LMICs and to identify specific factors affecting the occurrence of late burn complications. A systematic literature search was conducted to retrieve articles on pediatric burns in LMICs using Medline, Embase, the Cochrane Library, LILACS, Global Health, African Index Medicus, and others. Articles were assessed by two reviewers and reported in accordance with PRISMA guidelines. Of 2896 articles initially identified, 103 underwent full-text review and 14 met inclusion criteria. A total of 991 children who developed long-term burn sequelae were included. Time from injury to consultation ranged from a few months to 17 years. Factors associated with late complications included total body surface area burned, burn depth, low socio-economic status, limited infrastructure, perceived inability to pay, lack of awareness of surgical treatment, low level of maternal education, and time elapsed between burn injury and reconstructive surgery.